PENERAPAN MODEL PROBLEM BASED LEARNING BERBASIS DEEP LEARNING UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATERI STATISTIKA - Primandasari Hada Inda; Agnes Yuni Adrian; Rio Febrianto Arifendi; Nila Kartika Sari (Universitas Tribhuwana Tunggadewi, 2024)
This study was conducted to determine how the implementation of Deep learning–based Problem Based Learning (PBL) can help improve students’ understanding of data processing material at SMP Negeri 25 Malang. This research used a classroom action research method, with the subjects consisting of 30 students of class VIII-A at SMP Negeri 25 Malang. The data were collected through understanding tests, observations of the learning process, and interviews. The results of this study show that the implementation of Deep learning–based Problem Based Learning improved students’ understanding of data processing material. The average understanding score of the students increased significantly from the first cycle to the second cycle. In addition, students’ activity and engagement during the learning process also increased. The study concludes that the application of Deep learning–based Problem Based Learning can enhance students’ understanding of data processing material at SMP Negeri 25 Malang.